A NOVEL METHOD FOR VRANA SHODHANA & ROPANA USING KSHARAJALA - V. Shekokar, Anantkumar; M. Borkar, Kanchan (International Journal of Ayurveda and Pharma Research, 2015)
Indians have paid enough attention to discover the therapeutic effects of plants and herbs as medicinal agents in many diseases. Plants contain Alkaloids and various other chemical substances which form the base for many medical preparations. Most of the drugs used are derived from the natural world through the experiments of earlier civilization. Ksharajala is an innovative concept used for management of Infected & chronic Wounds and ulcers. This Ksharajala was prepared with the help of Apamargakshara & distilled water in 1:100 proportion. It can be used in number of open wounds & ulcers. This Ksharajala is prepared similar to the Hima kalpana preparation. There are number of dressing materials given by Sushruta e.g. Pichu, Kawalika, Plota and Vikeshika or Varti, Kashaya, Kwatha, Rasakriya, Swarasa, Lepa and Hima. Ksaharajala as a dressing material which can be used as for deep & broader wounds & ulcers. In the present study preparation of Ksharajala, advantages, indications, disadvantages, sterilization, storage, standardization were observed for simple & safest parasurgical practice.